Penerapan Pemidanaan terhadap Pelaku Kejahatan Orang dengan Gangguan Jiwa (ODGJ) (Neolectura, 2023)
There are many aspects that must be reviewed in responding to criminal acts, one of which is related to the psychology of criminals. Hence, the problem arises which can be explained by the formulation of the concept or form of punishment according to criminal theory against people with mental disorders and how legal arrangements are related to crime with perpetrators who have mental disorders. In the interest of law enforcement, a person suspected of having mental disorders due to an illness or more commonly called ODGJ who commits a crime must first get a mental health examination, if referring to several court decisions on existing discussions and regulations, then of course criminal renspobility by the perpetrator with mentally disturbed due to illness still implemented. However, first a psychiatric and psychological examination must be carried out to determine whether the person has a mental disorder or not. After it is definitely diagnosed that there is a disturbance in the perpetrators soul which causes him to be unable to take rensposiblity for his actions, treatment related to his illness will be carried out first.